Low Vitamin D Levels Increase the Risk of Early Onset Neonatal Sepsis: Kadar vitamin D yang Rendah Meningkatkan Risiko Sepsis Neonatal Awitan Dini - Lisnawati Yuyun; Ali Sungkar; Rinawati Rohsiswatno; Noroyono Wibowo; Denni Hermartin; Agustin Kindi (Indonesian Journal of Obstetrics and Gynecology, 2020)
Abstract Objective: To identify the association between maternal and umbilical cord vitamin D levels with suspects of early-onset of neonatal sepsis (EONS) in newborns from mothers with preterm premature rupture of membranes (PPROM).Methods: This is a retrospective cohort study conducted from January 2017 to Augusts 2018. Data was taken consecutively from medical records and previous study data at Dr. Cipto Mangunkusumo and Persahabatan Hospital, Jakarta.Results: From total of 72 infants from mothers with PPROM, 22 infants (31%) were EONS-suspected and 50 infants (69%) were not EONS-suspected. There was a significant association between maternal and umbilical cord vitamin D levels with EONS.Conclusion: There was a significant association between maternal and umbilical cord vitamin D levels with EONS.Keywords: early-onset neonatal sepsis, preterm premature rupture of membrane, vitamin D, Abstrak Tujuan: Untuk mengetahui hubungan antara kadar vitamin D maternal dan tali pusat dengan risiko tejadinya Sepsis Neonatal Awitan Dini (SNAD) pada bayi dari ibu dengan Ketuban Pecah Dini (KPD).Metode: Desain penelitian kohort retrospektif secara consecutive sampling. Data diambil dari rekam medis dan data penelitian sebelumnya di Rumah Sakit Umum Pusat Nasional (RSUPN) Dr. Cipto Mangunkusumo dan Rumah Sakit Umum Pusat (RSUP) Persahabatan, Jakarta. Hasil: Dari 72 bayi yang dilahirkan dari ibu dengan KPD, 22 bayi (31%) diantaranya diduga mengalami SNAD, sedangkan 50 bayi lainnya tidak mengalami SNAD. Terdapat hubungan yang bermakna antara kadar vitamin D maternal dan tali pusat dengan kejadian SNAD. Kesimpulan:Terdapathubungan yang bermakna antara kadar vitamin D maternal dan tali pusat dengan kejadian SNAD.Kata kunci: ketuban pecah dini, sepsis neonatal awitan dini, vitamin D